The Implementation of Primary School’s Literacy Movement in Bekasi - Ika Chairiyani (LPTK IAIN Kediri, 2023)
Gerakan Literasi Sekolah (Literally, School Literacy Movement) is a government program to increase students’ interests in reading from the primary level to university level. This program has been carried out in SD Hasanah Qur’anic School since 2019. This research was due to describe the implementation of SLM and to describe the stages of SLM at SD Hasanah Qur’anic School. This research used qualitative research methodology which focus on a descriptive study. The focus of this research was fifth grade students of SD Hasanah Qur’anic School, Bekasi. To carry out the data, the researcher utilized observation and in-depth interview. The results showed that class VI was enthusiastic to participate in the program. Teachers implemented the program using fun activities. However, the limitation of resource books influenced students’ reading experience. Besides, most students reported that they did not have sufficient resource books at home.